2021
DOI: 10.31557/apjcp.2021.22.11.3601
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Rivaroxaban Use in Solid Tumour Malignancy: Experience from a Tertiary Care Cancer Centre

Abstract: a hypercoagulable state (Goldhaber and Bounameaux, 2012). Besides that, interaction among cancer cells, host cells, venous stasis, vessel wall injury, and cancer treatment itself has been associated with CAT (Ay et al., 2017). It significantly causes morbidity resulting due to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…26 Despite the limited proportion of DOAC users in our cohort, we can conclude that DOACs are a viable alternative to LMWH on the basis of our results. For recurrent VTE outcomes, we observed similar rates between DOACs and LMWH, which is consistent with previous real-world studies, 25,27 However, this differs from the SELECT-D study, 9 which reported lower VTE recurrence with rivaroxaban compared with dalteparin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…26 Despite the limited proportion of DOAC users in our cohort, we can conclude that DOACs are a viable alternative to LMWH on the basis of our results. For recurrent VTE outcomes, we observed similar rates between DOACs and LMWH, which is consistent with previous real-world studies, 25,27 However, this differs from the SELECT-D study, 9 which reported lower VTE recurrence with rivaroxaban compared with dalteparin.…”
Section: Discussionsupporting
confidence: 90%
“…The present study supports previous observational studies that have shown comparable bleeding rates between DOACs and LMWH, 10 , 12 , 13 thus strengthening the real-world safety of DOACs in Thailand and similar health care settings. Most real-world studies, 13 , 27 including this one, predominantly involve patients treated with rivaroxaban as it is the most used DOACs. Because of the limited number of patients who received apixaban, edoxaban, and dabigatran, it was not possible to conduct a meaningful comparison among the different DOACs.…”
Section: Discussionmentioning
confidence: 99%